Evaluation of Dynamic Contrast‐Enhanced MRI Measures of Lung Congestion and Endothelial Permeability in Heart Failure: A Prospective Method Validation Study. Issue 2 (27th March 2022) - Cheriyan, Joseph; Roberts, Alexandra; Roberts, Caleb; Graves, Martin J.; Patterson, Ilse; Slough, Rhys A.; Schroyer, Rosemary; Fernando, Disala; Kumar, Subramanya; Lee, Sarah; Parker, Geoffrey J.M.; Sarov‐Blat, Lea; et al.
Abstract : Background: Methods for accurate quantification of lung fluid in heart failure (HF) are needed. Dynamic contrast‐enhanced (DCE)‐MRI may be an appropriate modality. Purpose: DCE‐MRI evaluation of fraction of fluid volume in the interstitial lung space ( v e ) and vascular permeability ( K trans ). Study Type: Prospective, single‐center method validation. Population: Seventeen evaluable healthy volunteers (HVs), 12 participants with HF, and 3 with acute decompensated HF (ADHF). Field Strength/Sequence: T 1 mapping (spoiled gradient echo variable flip angle acquisition) followed by dynamic series (three‐dimensional spoiled gradient‐recalled echo acquisitions [constant echo time, repetition time, and flip angle at 1.5 T]). Assessment: Three whole‐chest scans were acquired: baseline (Session 1), 1‐week later (Session 2), following exercise (Session 3). Extended Tofts model quantified v e and K trans (voxel‐wise basis); total lung median measures were extracted and fitted via repeat measure analysis of variance (ANOVA) model. Patient tolerability of the scanning protocol was assessed. Statistical Tests: This was constructed as an experimental medicine study. Primary endpoints: K trans and v e at baseline (HV vs. HF), change in K trans and v e following exercise, and following lung congestion resolution (ADHF). K trans and v e were fitted separately using ANOVA. Secondary endpoint: repeatability, that is, within‐participant variability in v e and K trans between sessions (coefficient of variation estimated via mixed effects model). Results: There was no significant difference in mean K trans between HF and HV ( P ≤ 0.17): 0.2216 minutes −1 and 0.2353 minutes −1 (Session 1), 0.2044 minutes −1 and 0.2567 minutes −1 (Session 2), 0.1841 minutes −1 and 0.2108 minutes −1 (Session 3), respectively. v e was greater in the HF group (all scans, P ≤ 0.02). Results were repeatable between Sessions 1 and 2; mean values for HF and HV were 0.4946 and 0.3346 (Session 1), 0.4353 and 0.3205 (Session 2), respectively. There was minimal difference in K trans or v e between scans for participants with ADHF (small population precluded significance testing). Scanning was well tolerated. Data Conclusion: While no differences were detected in K trans, v e was greater in chronic HF patients vs. HV, augmented beyond plasma and intracellular volume. DCE‐MRI is a valuable diagnostic and physiologic tool to evaluate changes in fluid volume in the interstitial lung space associated with symptomatic HF. Level of Evidence: 2 Technical Efficacy Stage: 2